Benefit of Hybrid Learning in Education Using of Reusable Mask to Mothers During The Covid19 Pandemic in Pekanbaru - Ingrid Weddy Viva Febrya (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
This study aims to see whether the given of education using hybrid learning method to mothers as the first school at home in protecting the environment through the use of reusable masks (re-washing) is effective in overcoming the accumulation of disposable mask waste during the Covid-19 pandemic. The use of disposable masks has the potential to become a problem of accumulating rubbish that has the potential to earth damage, especially during the pandemic. The use of repeated washing masks and an understanding of their care and maintenance can help these problems. Mothers who are teachers in the family are the right target to be given socialization on the use of washing masks so that they become an extension of the government in helping address environmental problems. The hybrid learning method is deemed suitable to be used during the pandemic to suppress virus transmission. The research was conducted in Agust - October 2021. The place where the research was carried out was at IMH PSIKOLATES Pekanbaru. This research uses qualitative methods and is described in a descriptive way. The research subjects were 10 mothers, selected purposively with the following criteria: 1) aged 30 years - 55 years, 2) having children more than 1, 3) domicile in the city of Pekanbaru. Based on the results of the study, it was found that the hybrid learning method in educating mothers about the use of re-washing masks and maintaining their cleanliness was useful in helping reduce disposable mask waste, especially during the Covid19 pandemic.